The effect of long-term supplemental dietary cadmium on lipid peroxidation and the antioxidant system in the liver and kidneys of rabbits - Beytut, E; Aksakal, M (Tubitak Scientific & Technological Research Council Turkey, 2002)
We investigated the effects of chronic exposure to dietary cadmium (Cd) on the levels of lipid peroxidation (LPO) and reduced glutathione (GSH) associated with activities of glutathione peroxidase (GSH-Px) and the catalase (CAT) enzyme in the liver and kidneys of rabbits. Twenty 10-month-old clinically healthy New Zealand white rabbits (10/group) of 3545 +/- 250 g average body weight were used. The control group was allowed to take food and tap water ad libitum, while the experimental group was given tap water containing 200 ppm CdCl2/L for 28 weeks. Lipid peroxidation contents increased significantly in the liver (p < 0.001) and kidneys (p < 0.005) of Cd-treated rabbits. Glutathione levels decreased significantly in both the liver (p < 0.001) and the kidneys (p < 0.005) of the experimental group. Cadmium treatment caused a significant decrease in the activities of GSH-Px and CAT in the liver (p < 0.001, p < 0.01) and kidneys (p < 0.005, p < 0.1) of the rabbits. These results indicated that a Cd-induced increase in LPO was associated with reductions in GSH-Px and CAT enzyme activities, and in GSH levels in the liver and kidneys of rabbits.
Keywords: cadmium; lipid peroxidation; glutathione peroxidase; catalase; glutathione; rabbit